1994
DOI: 10.1073/pnas.91.18.8695
|View full text |Cite
|
Sign up to set email alerts
|

Deficient induction of human hsp70 heat shock gene transcription in Y79 retinoblastoma cells despite activation of heat shock factor 1.

Abstract: One ofthe basic features of the inducible heat shock response is the activation of heat shock factor which results in the rapid transcriptional induction of the heat shock genes. Although it is widely considered that the heat shock response is ubiquitous, several reports have indicated that the transcriptional response can vary in both intensity and kinetics and often in a tissue-specific manner. Of interest have been studies on the expression of heat shock genes in the brain, particularly observations that ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 42 publications
1
34
1
Order By: Relevance
“…Notably, a constitutively active mutant of HSF1 (⌬HSF) very efficiently induced expression of Hsp72, showing that the endogenous Hsp72 gene in ScN2a cells has a functional promoter. This is in contrast to some cell lines described earlier (20, 64 -66) in which a chromatin-mediated effect accounted for an impaired Hsp72 expression after stress (67,68). Based on the finding that in ScN2a cells HSF1 activity after stress was sufficient to induce trimer formation yet insufficient to promote transactivation competence, we directed our attention to the activation/deactivation pathway of HSF1.…”
Section: Discussioncontrasting
confidence: 47%
“…Notably, a constitutively active mutant of HSF1 (⌬HSF) very efficiently induced expression of Hsp72, showing that the endogenous Hsp72 gene in ScN2a cells has a functional promoter. This is in contrast to some cell lines described earlier (20, 64 -66) in which a chromatin-mediated effect accounted for an impaired Hsp72 expression after stress (67,68). Based on the finding that in ScN2a cells HSF1 activity after stress was sufficient to induce trimer formation yet insufficient to promote transactivation competence, we directed our attention to the activation/deactivation pathway of HSF1.…”
Section: Discussioncontrasting
confidence: 47%
“…Of particular interest are studies on the HSR in the brain and during aging (Sprang and Brown 1987;Blake et al 1991;Shamovsky and Gershon 2004) that have observed restricted expression of HS in different regions of the brain. Likewise, for neuronal cells in culture, the selective induction of HS genes has been observed; for example, in human neuroblastoma Y79 cells, HSF-1 is activated yet transcription of the Hsp90 but not Hsp70 gene is observed (Mathur et al 1994). In primary hippocampal neurons from neonatal rat embryos, only HSF-2 but not HSF-1 is expressed; consequently, hippocampal neurons are deficient for the HSR, whereas cocultured astrocytes exhibit a robust HSR (Marcuccilli et al 1996).…”
Section: Stress-inducible Regulation Of Chaperone Networkmentioning
confidence: 99%
“…Although the importance of HSF1 in the regulation of mammalian hsp70 expression is well-established, recent data indicate that activation of HSF1 is not sufficient for the induction of hsp70 gene expression (36,39,43). Studies from our laboratory and others suggest the existence of an additional regulatory factor or factors (18,36).…”
mentioning
confidence: 93%